Techno-Entrepreneurship Learning Model in Higher Education - Alfrina Mewengkang; Johan Reimon Batmetan (Elinvo (Electronics, Informatics, and Vocational Education), 2021)
Techno-Entrepreneurship becomes an important part of higher education based on information technology. This is useful to enhance the spirit of entrepreneurship, the ability to read opportunities and build information technology-based businesses. This study aims to examine the appropriate techno-entrepreneurship learning model in higher education. The research method used is action research with practice using lean canvas models for business models and design sprint method to build product prototypes. The results of this study show how to use practice and tutorials, students can create the right business model and be able to make a prototype of a digital product that is good in implementing business ideas. The conclusion obtained in this study is that techno-entrepreneurship is very appropriate to use lean canvas to build business models and more efficiently use sprint designs to build prototypes of digital products. This model is highly recommended for entrepreneurship learning in higher education.